Lithium-sodium composite manganese-based material and preparation method thereof, positive pole piece, secondary battery and electric device

CN119744448APending Publication Date: 2025-04-01CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380061141.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-05-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based positive electrode materials have problems such as low first-effect, low gram capacity, poor circulation and gas production, which limits their application in lithium-ion batteries.

Method used

The LitNay[LixNiaCobMncMd]ApOq structure is formed by doping Na elements at the lithium position, doping metal elements with high valence or large ion radius at the manganese position, and doping anions at the oxygen position, thereby improving the first and improve gas production by doping the combination of transition metals such as Ni, Co, Mn and oxygen.

Benefits of technology

The first Coulomb efficiency and capacity of lithium-sodium composite manganese-based materials have been significantly improved, circulating performance and gas production behavior have been improved, and the internal resistance and cost of the battery have been reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a lithium-sodium composite manganese-based material and a preparation method thereof, a positive pole piece, a secondary battery and an electric device. The lithium-sodium composite manganese-based material comprises LitNay [LixNiaCobMncMd] ApOq, wherein 0 < y < = 0.2, 0.68 < = t + y < = 1, x + a + b + c + d = 1, x > 0, a > = 0.17, 0 < = b < 0.1, c > = 0.4, 0 < = d < 0.04, 0 < = p < = 0.1, and 0 < q < = 2; m comprises one or more of V, Nb, Ta, Cr, Mo, B, Al, Ti, Zr, Mg, Ce, Fe, W or Sn, and A comprises one or more of F, S, N or Cl. The lithium-sodium composite manganese-based material provided by the invention has high first efficiency and gram volume, good cycle performance and low gas production.
Need to check novelty before this filing date? Find Prior Art

Description

Lithium-sodium composite manganese-based material, its preparation method, positive electrode sheet, secondary battery and electrical device Technical Field

[0001] This application relates to the technical field of batteries, and specifically relates to a lithium-sodium composite manganese-based material, its preparation method, positive electrode sheet, secondary battery and electrical device. Background Art

[0002] The positive electrode material is a key component of the battery, affecting the performance of the battery such as capacity and cycle stability. In lithium-ion batteries, common positive electrode materials include lithium iron phosphate, lithium cobaltate, nickel cobalt manganese ternary materials, nickel cobalt aluminum ternary materials, etc.

[0003] Among the currently known positive electrode materials, lithium-rich manganese-based positive electrode materials have received wide attention due to their high discharge specific capacity. However, the existing lithium-rich manganese-based positive electrode materials generally have problems such as low initial efficiency (initial cycle Coulomb efficiency), low specific capacity per gram, poor cycling performance, high gas generation, etc., which restrict their development.

[0004] Summary of the Invention

[0005] In view of the above problems, this application provides a lithium-sodium composite manganese-based material, its preparation method, positive electrode sheet, secondary battery and electrical device, which can solve the technical problems such as low initial efficiency, low specific capacity per gram, poor cycling performance, and high gas generation existing in the lithium-sodium composite manganese-based material.

[0006] In a first aspect, this application provides a lithium-sodium composite manganese-based material, which includes Li

[0007] Na y [Li x Ni a Co b Mn c M d A p O q , where 0 < y ≤ 0.2, .68 ≤ t + y ≤ 1, x + a + b + c + d = 1, x > 0, a ≥ 0.17, 0 ≤ b < 0.1, c ≥ 0.4, 0 ≤ d < 0.04, 0 ≤ p ≤ 0.1, 0 < q ≤ 2; M includes one or more of V, Nb, Ta, Cr, Mo, B, Al, Ti, Zr, Mg, Ce, Fe, W or Sn, and A includes one or more of F, S, N or Cl.

[0007] In the lithium sodium composite manganese-based material of the present application, some Na elements are doped on the Li position, and in addition to Ni and Co, M elements are also doped on the Mn position, and A elements are doped on the oxygen position. Because there are many vacant active sites that can be incorporated into Li in the structure formed by Na elements and transition metal elements such as Ni, Co, and Mn, and the increase of Li active sites is beneficial to the first efficiency and gram capacity, the first coulomb efficiency and gram capacity can be significantly improved for low-cobalt manganese-rich positive electrode materials. Because the extraction and insertion of Li / Na elements are accompanied by large volume and stress changes, the present application incorporates M elements with high valence or large ionic radius such as V into the bulk phase, which can serve as pinning points to stabilize the lattice after a large amount of Li / Na is removed; by adding A elements such as F into the bulk phase, the combination of transition metals such as Ni, Co, and Mn with oxygen elements can be stabilized, and the large amount of oxygen release caused by the anion redox reaction of manganese-rich materials under high voltage is improved, thereby improving the gas production of the material. In short, the lithium-sodium composite manganese-based material of the present application can not only improve the first efficiency and gram capacity by using a Na phase rich in active sites in an appropriate proportion, but also improve the structural stability of the material in the electrochemical process by doping cations M and anions A, thereby improving the cycle performance and gas production behavior of the material.

[0008] In some embodiments, 0 < y ≤ 0.1. In the lithium-sodium manganese-based composite material of the present application, the amount of Na incorporated cannot be higher than 20% of the total molar amount of Li, that is, 0 < y ≤ 0.2. Alternatively, 0 < y ≤ 0.1. An amount of Na incorporated higher than 20% of the total molar amount of Li will exceed the limit of Na ion throughput that the graphite negative electrode in the traditional lithium-ion battery chemical system can withstand. Therefore, setting the amount of Na incorporated within an appropriate range can meet the throughput limit of the negative electrode in traditional lithium-ion batteries.

[0009] In some embodiments, the mass percentage of the Na element in the lithium-sodium composite manganese-based material is less than or equal to 6%; optionally, the mass percentage is greater than or equal to 0.3% and less than or equal to 2%.

[0010] In some embodiments, the specific surface area of ​​the lithium sodium composite manganese-based material is 0.3 to 12 m 2 / g; optionally 0.4~10m 2 / g; optionally 0.5~5.5m 2 / g. A suitable specific surface area range helps achieve higher gram capacity, first coulombic efficiency and cycle life, as well as lower gas production.

[0011] In some embodiments, the mass fraction of alkaline substances in the lithium-sodium manganese composite material is 250 to 3000 ppm; alternatively, 300 to 3000; alternatively, 300 to 2000 ppm. The mass fraction of alkaline substances can also be referred to as residual alkali. The residual alkali content has a significant impact on the performance of the positive electrode material and the battery preparation process. The lithium-sodium manganese composite material of the present application has an appropriate residual alkali content, which helps to achieve lower internal resistance, higher gram capacity, and ensure the processing performance of the positive electrode slurry.

[0012] In some embodiments, the X-ray diffraction pattern of the lithium sodium composite manganese-based material includes a (101) crystal plane diffraction peak at a 2θ angle of 36.5±0.5° and a (102) crystal plane diffraction peak at a 2θ angle of 38.4±0.5°, and the (101) crystal plane diffraction peak and the (102) crystal plane diffraction peak satisfy the following conditions: (I 101 / I 102 ) 0.5 ≥1.96, where I 101 represents the peak area of ​​the (101) crystal plane diffraction peak, the I 102 represents the peak area of ​​the (102) crystal plane diffraction peak; optionally, (I 101 / I 102 ) 0.5 ≥2. Oxygen defects are an important influencing factor of positive electrode materials, which refers to the detachment of oxygen atoms (oxygen ions) in the crystal lattice, resulting in oxygen deficiency and the formation of vacancies, that is, defects left behind by the escape of oxygen atoms (oxygen ions) from its crystal lattice. Oxygen defects can have a significant impact on the performance of the material, such as the charge and discharge capacity, cycle performance, and rate performance of the positive electrode material. For the lithium-sodium manganese composite material of the present application, its (101) crystal plane oxygen defects have no contribution, while the (102) crystal plane has a negative contribution to oxygen defects. Therefore, the peak area ratio of the crystal plane diffraction peaks of the two can reflect the oxygen defect content and the presence of oxygen defects in the lithium-sodium manganese composite material. In the present application, (I 101 / I 102 ) 0.5 ≥1.96, which helps to form lithium-sodium manganese composite-based materials with lower oxygen defects, thereby improving the gram capacity, first efficiency, cycle performance and gas production of lithium-sodium manganese composite-based materials.

[0013] In some embodiments, the X-ray diffraction pattern of the lithium sodium composite manganese-based material includes a (002) crystal plane diffraction peak at a 2θ angle of 16.0±0.8° and a (003) crystal plane diffraction peak at a 2θ angle of 18.6±0.6°, and the (002) crystal plane diffraction peak and the (003) crystal plane diffraction peak satisfy: 0≤(I 002 / I 003 )≤0.4, where I 002represents the peak area of ​​the (002) crystal plane diffraction peak, I 003 represents the peak area of ​​the (003) crystal plane diffraction peak; optionally, 0.01≤(I 002 / I 003 )≤0.4. (002) and (003) crystal planes are related to the Na content, and the appropriate (I 002 / I 003 ) range helps to form a lithium-sodium composite manganese-based material with an appropriate proportion of Na-containing phases.

[0014] In some embodiments, the lithium-sodium manganese composite material has a median particle size Dv50 of 2 to 15 μm, or optionally 3 to 10 μm. The lithium-sodium manganese composite material of the present application has a suitable median particle size, which facilitates the formation of a suitable specific surface area. Furthermore, the micron-scale median particle size reduces the requirements for the preparation process, thus helping to control costs.

[0015] In some embodiments, the particle size distribution span (SPAN) of the lithium-sodium manganese composite material is in the range of [(Dv90 - Dv10) / Dv50]: 0.5 ≤ SPAN ≤ 2; alternatively, 0.5 ≤ SPAN ≤ 1.8; alternatively, 0.8 ≤ SPAN ≤ 1.4. Particle size distribution significantly impacts the processing of positive electrode materials, and the SPAN range of this application helps achieve a higher electrode compaction density.

[0016] In some embodiments, (t+x) / (a+b+c)=0.9-1.4, optionally (t+x) / (a+b+c)=1.3-1.4. (t+x) / (a+b+c) represents the molar ratio of Li, Ni, Co, and Mn in the lithium-sodium manganese composite material. At an appropriate ratio of Li, Ni, Co, and Mn, the cations are increased and mixed in the lithium-sodium manganese composite material, thereby improving the cycling performance.

[0017] In a second aspect, the present application provides a method for preparing a lithium-sodium composite manganese-based material, comprising:

[0018] Mixing raw materials and performing a first sintering process; the raw materials include a lithium source, a sodium source, a nickel source and a manganese source, and optionally also include a cobalt source, an M source and an A source;

[0019] Wherein, the lithium sodium composite manganese-based material includes Li t Na y [Li x Ni a Co b Mn c M d ]A p O q, 0 < y ≤ 0.2, 0.68 ≤ t + y ≤ 1, x + a + b + c + d = 1, x > 0, a ≥ 0.17, 0 ≤ b < 0.1, c ≥ 0.4, 0 ≤ d < 0.04, 0 ≤ p ≤ 0.1, 0 < q ≤ 2; M comprises one or more of V, Nb, Ta, Cr, Mo, B, Al, Ti, Zr, Mg, Ce, Fe, W or Sn, and A comprises one or more of F, S, N or Cl.

[0020] In the preparation method of the present application, first, each raw material is mixed and subjected to a first sintering treatment, so that Na element is doped into the lithium site, M element is doped into the manganese site, and A element is doped into the oxygen site, simultaneously achieving the doping of Na, M and A. The lithium-sodium composite manganese-based material prepared by this method has both high specific capacity, high initial Coulomb efficiency, good cycling performance, and the gas generation situation is effectively improved. At the same time, the preparation method of the present application is simple to operate, suitable for mass production, with low cost and high efficiency.

[0021] In some embodiments, the conditions of the first sintering treatment include one or more of the following (1) to (4):

[0022] (1) The temperature of the first sintering treatment is 700 - 1100 °C, optionally 750 - 1000 °C;

[0023] [[ID=;12]](2) Heating to the temperature of the first sintering treatment at a rate of 2 - 10 °C / min; <;

[0024] (3) Keeping the temperature for 10 - 20 h at the temperature of the first sintering treatment;

[0025] (4) An oxygen-containing atmosphere.

[0026] Suitable sintering treatment conditions are beneficial to the formation of a composite oxide material with high crystallinity and good doping effect from lithium source, sodium source, nickel source, cobalt source, manganese source, M source and A source, and preparing a lithium-sodium composite manganese-based material with both high specific capacity, high initial Coulomb efficiency, good cycling performance, and the gas generation situation is effectively improved.

[0027] In some embodiments, the conditions of the first sintering treatment include one or more of the following (1) to (4):

[0028] (1) The temperature of the first sintering treatment is 780 - 990 °C;

[0029] (2) Heating to the temperature of the first sintering treatment at a rate of 2 - 5 °C / min;

[0030] (3) Keeping the temperature for 10 - 15 h at the temperature of the first sintering treatment;

[0031] (4) An oxygen-containing atmosphere, wherein the volume percentage of oxygen in the oxygen-containing atmosphere is 20% to 99.99%.

[0032] In some embodiments, the method for preparing the lithium-sodium composite manganese-based material further comprises a step of washing the product of the first sintering treatment.

[0033] After the first sintering treatment, alkaline substances such as sodium hydroxide, lithium hydroxide, sodium carbonate, and lithium carbonate often remain. The amount of residual alkaline has a significant impact on the performance of the positive electrode material and the battery manufacturing process. By performing a washing step after the first sintering treatment, the residual alkaline content of the lithium-sodium manganese composite material can be adjusted, helping to achieve lower internal resistance, higher gram capacity, and ensure the processing performance of the positive electrode slurry.

[0034] In some embodiments, the washing step includes washing the product of the first sintering treatment with a washing solution; optionally, the pH range of the washing solution is 1.5 to 7, optionally 2 to 7, and optionally 2.5 to 7. By treating the product of the first sintering treatment with an acidic or neutral washing solution, an acid-base neutralization reaction can occur, or the residual alkali concentration of the product of the first sintering treatment can be adjusted by washing or dilution to obtain a suitable residual alkali amount, which helps to achieve lower internal resistance, higher gram capacity, and ensure the processing performance of the positive electrode slurry.

[0035] In some embodiments, the solid-to-liquid ratio of the product of the first sintering treatment to the washing liquid is 1 / 35 to 1 / 6 g / mL; alternatively, 1 / 20 to 1 / 10 g / mL. A suitable solid-to-liquid ratio allows repeated washing of the product of the first sintering treatment to adjust the residual alkali content of the material.

[0036] In some embodiments, the washing treatment time is 0.2 to 10 hours; optionally, 0.25 to 4 hours.

[0037] In some embodiments, the washing process includes a stirring step, and the stirring rate is 800-1200 r / min, optionally 900-1000 r / min. Through appropriate washing process conditions, the first sintered product can be repeatedly washed to adjust the residual alkali content of the material.

[0038] In some embodiments, the washing liquid includes one or more of water and an acidic solution; optionally, the acidic solution includes a solution of one or more of hydrochloric acid, sulfuric acid, nitric acid, acetic acid, citric acid, ammonium citrate, phosphoric acid, ammonium chloride, and ammonium sulfate. Such acids or acidic salts can form an acidic solution to neutralize the product of the first sintering treatment without introducing impurity ions into the lithium-sodium composite manganese-based material.

[0039] In some embodiments, the method for preparing the lithium-sodium manganese composite material further includes subjecting the product of the first sintering treatment to a second sintering treatment. The second sintering treatment can improve the crystallinity and oxygen deficiency of the lithium-sodium manganese composite material, thereby improving the specific capacity, initial efficiency, cycle performance, and gas production of the lithium-sodium manganese composite material. In some embodiments, when the first sintering treatment step is followed by both a washing treatment step and a second sintering treatment step, the second sintering treatment step can be performed after the washing treatment step.

[0040] In some embodiments, the conditions of the second sintering treatment include one or more of the following (i) to (iv):

[0041] (i) the temperature of the second sintering treatment is 300-700° C., optionally 300-600° C.;

[0042] (ii) heating the mixture to the second sintering temperature at a rate of 2 to 10° C. / min;

[0043] (iii) maintaining the temperature at the second sintering treatment for 5 to 20 hours;

[0044] (iv) Oxygen-containing atmosphere.

[0045] Carrying out a second sintering treatment under appropriate conditions can improve the crystallinity and oxygen defects of the lithium-sodium manganese composite-based material, which is beneficial to improving the gram capacity, first efficiency, cycle performance and gas production of the lithium-sodium manganese composite-based material.

[0046] The conditions of the second sintering treatment include one or more of the following (i) to (iv):

[0047] (i) the temperature of the second sintering treatment is 400-550° C.;

[0048] (ii) heating the mixture to the second sintering temperature at a rate of 2 to 5°C / min;

[0049] (iii) maintaining the temperature at the second sintering treatment for 8 to 12 hours;

[0050] (iv) an oxygen-containing atmosphere, wherein the volume percentage of oxygen in the oxygen-containing atmosphere is 20% to 99.99%.

[0051] In a third aspect, the present application provides a positive electrode plate, which includes the lithium-sodium composite manganese-based material as described above, or includes the lithium-sodium composite manganese-based material prepared by the method described above.

[0052] The lithium-sodium composite manganese-based material of the present application can be used as the active material of the positive electrode plate, which helps to achieve higher battery capacity, first coulombic efficiency and cycle performance, and improve battery gas production.

[0053] In a fourth aspect, the present application provides a secondary battery, which includes the above-mentioned positive electrode plate.

[0054] The positive electrode plate containing the lithium-sodium composite manganese-based material of the present application is applied to a secondary battery, and the secondary battery has high capacity, first coulombic efficiency and cycle performance, and low gas production.

[0055] In a fifth aspect, the present application also provides an electrical device, which includes the above-mentioned secondary battery.

[0056] The secondary battery disclosed in the embodiments of the present application can be used in electrical devices that use the battery as a power source, or various energy storage systems that use the battery as an energy storage element. Electrical devices may include, but are not limited to, mobile phones, tablets, laptops, electric toys, power tools, battery cars, electric cars, ships, spacecraft, and the like. Among them, electric toys may include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, and the like, and spacecraft may include airplanes, rockets, space shuttles, and spacecraft, and the like.

[0057] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. DETAILED DESCRIPTION

[0058] The following embodiments of the technical solution of the present application will be described in detail with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application and are therefore only examples and are not intended to limit the scope of protection of the present application.

[0059] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned figure descriptions are intended to cover non-exclusive inclusions.

[0060] In the description of the embodiments of this application, the technical terms "first" and "second" are used only to distinguish different objects and should not be understood to indicate or imply relative importance or implicitly specify the quantity, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "plurality" is more than two, unless otherwise clearly and specifically defined.

[0061] References herein to "embodiments" mean that a particular feature, structure, or characteristic described in connection with the embodiments may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor does it constitute an independent or alternative embodiment that is mutually exclusive of other embodiments. It is understood, both explicitly and implicitly, by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0062] In the description of the embodiments of this application, the term "and / or" is simply a description of the association relationship between associated objects, indicating that three relationships can exist. For example, A and / or B can represent the following three situations: A exists alone, A and B exist simultaneously, and B exists alone. In addition, the character " / " in this document generally indicates that the associated objects are in an "or" relationship.

[0063] In the description of the embodiments of the present application, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c" can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0064] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. Some or all of the steps can be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0065] The masses of the relevant components mentioned in the examples of this application may not only refer to the specific content of each component, but also represent the proportional relationship between the masses of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the examples of this application, it is within the scope disclosed in the examples of this application. Specifically, the masses described in the examples of this application may be mass units known in the chemical industry, such as μg, mg, g, and kg.

[0066] Lithium-ion batteries, due to their high capacity, long lifespan, and environmentally friendly characteristics, are widely used as secondary energy storage devices in consumer electronics, electric vehicles, electric bicycles, and other fields. With the continuous progress of society and the development of science and technology, higher requirements are being placed on secondary energy storage devices, such as lithium-ion batteries, requiring them to have higher capacity, longer lifespan, and greater safety. One of the key factors in achieving these requirements lies in the cathode material.

[0067] Currently known cathode materials include lithium cobalt oxide, lithium iron phosphate, nickel-cobalt-manganese or nickel-cobalt-aluminum ternary cathode materials, and lithium-rich manganese-based layered oxide cathode materials (lithium-rich manganese-based cathode materials). These cathode materials have either been commercialized or are still in the experimental research and development stage. Among them, lithium-rich manganese-based cathode materials have attracted widespread attention due to their extremely high theoretical specific capacity and reversible capacity.

[0068] The physical phases in lithium-rich manganese-based materials are relatively complex and no conclusion can be given at present, but it is generally believed that they mainly contain different lithium manganese oxide phases. During the first charge, part of the lithium manganese oxide phase in the lithium-rich manganese-based material is activated, which then leads to irreversible lithium ion removal and oxygen release. In addition, during the battery cycle, cation rearrangement and structural transformation occur, resulting in lower first efficiency and capacity decay, accompanied by more serious gas production problems. To solve the above technical problems, related technologies improve the lithium ion diffusion channel by forming layered oxides in lithium-rich manganese-based positive electrode materials, thereby improving the first efficiency, cycle performance and rate performance of the positive electrode material. Or by adjusting the content of specific crystal planes in the lithium-rich manganese-based positive electrode material, the capacity and cycle performance of the positive electrode material are improved. There are also related studies that involve regulating the morphology of lithium-rich manganese-based positive electrode materials, such as designing them into nanorods, nanowires, nanotubes, nanosheets and other forms. Such structures can shorten the diffusion path of electrons and lithium ions, which is helpful for improving the capacity and cycle performance of the material. Other related technologies adjust the lattice parameters by doping metal elements such as Ni and Co at the manganese position to improve the initial efficiency, capacity, and cycle performance of the cathode material. However, in practice, it has been found that such technologies generally have a low degree of improvement in the initial efficiency, specific capacity, and cyclability of the cathode material. At the same time, irreversible oxygen release is inevitably caused, and the gas production of the cathode material cannot be improved.

[0069] The initial efficiency and gram capacity of lithium-rich manganese-based cathode materials are related to the amount of lithium ions available for deintercalation and intercalation. The cyclability of lithium-rich manganese-based cathode materials is affected by the reversibility of lithium-ion deintercalation and intercalation, while the release of oxygen is affected by the gassing problem. Therefore, by doping lithium-rich manganese-based cathode materials with specific elements, specifically by doping some lithium sites in the crystal lattice of lithium-rich manganese-based cathode materials with Na, the structure formed by Na and transition metal elements such as Ni, Co, and Mn contains many vacant active sites that can accommodate Li, which is conducive to the formation of reversible lithium-ion deintercalation and intercalation, thereby improving the initial coulombic efficiency and gram capacity. At the same time, since the extraction and insertion of Na elements are accompanied by large volume and stress changes, by incorporating metal elements with high valence or large ionic radius into the bulk phase, the lattice after a large amount of Li / Na removal can be stabilized as a pinning effect, thereby improving the stability of the lattice during the cycle and thus improving the cycle performance of the positive electrode material; in addition, anion doping at the oxygen site can stabilize the combination of transition metals such as Ni, Co, and Mn with oxygen elements, and improve the large amount of oxygen release caused by the anion redox reaction of manganese-rich materials under high voltage, thereby improving the gas production of the material.

[0070] In this way, by simultaneously doping Na elements at the lithium site, doping suitable high-valent or large ionic radius metal elements at the manganese site, and doping anions at the oxygen site, a new lithium-sodium composite manganese-based material is formed. The first efficiency, gram capacity, and cyclability of this material will be greatly improved, and the oxygen release behavior will be suppressed, and the gas production will be reduced.

[0071] The lithium-sodium manganese-based composite material disclosed in the embodiments of this application can be used in positive electrode plates. As an active material, the lithium-sodium manganese-based composite material can form the active layer of the positive electrode plate alone or in combination with other positive electrode materials. When combined with a certain current collector, a positive electrode plate can be formed. This positive electrode plate can be used in secondary batteries and, in turn, in various electrical devices powered by secondary batteries.

[0072] The present application will be further described below with reference to the following examples. It should be understood that these examples are only used to illustrate the present application and are not intended to limit the scope of the present application.

[0073] The present invention provides a lithium sodium manganese composite material. The present invention provides a lithium sodium manganese composite material. t Na y [Li x Ni a Co b Mn c M d ]A p O q, where \(0 < y \leq 0.2\), \(0.68 \leq t + y \leq 1\), \(x + a + b + c + d = 1\), \(x > 0\), \(a \geq 0.17\), \(0 \leq b < 0.1\), \(c \geq 0.4\), \(0 \leq d < 0.04\), \(0 \leq p \leq 0.1\), \(0 < q \leq 2\); \(M\) includes one or more of \(V\), \(Nb\), \(Ta\), \(Cr\), \(Mo\), \(B\), \(Al\), \(Ti\), \(Zr\), \(Mg\), \(Ce\), \(Fe\), \(W\) or \(Sn\), and \(A\) includes one or more of \(F\), \(S\), \(N\) or \(Cl\).

[0074] In the lithium-sodium composite manganese-based material of the embodiment of the present application, part of the Na element is doped at the Li site. In addition to doping Ni and Co at the Mn site, the M element is also doped. At the same time, the A element is doped at the oxygen site. Since there are many vacant active sites that can incorporate Li in the structure formed by the Na element and transition metal elements such as Ni, Co, and Mn, and the increase in Li active sites is beneficial to the initial efficiency and specific capacity, for the low-cobalt rich-manganese cathode material, the initial efficiency can be significantly improved and the specific capacity can be increased. Because the deintercalation and intercalation of Li / Na elements are accompanied by large volume and stress changes, in the embodiment of the present application, the M element with a high valence or a large ionic radius such as V in the bulk phase can be used as a pinning point to stabilize a large amount of the lattice after Li / Na deintercalation, improve the stability of the lattice during cycling, and thus improve the cycling performance of the cathode material; doping the A element such as F in the bulk phase can stabilize the binding of transition metal elements such as Ni, Co, and Mn with oxygen elements, and improve the large amount of oxygen release behavior caused by the anion redox reaction of the rich-manganese material at high voltages, thereby improving the gas generation situation of the material. In short, the lithium-sodium composite manganese-based material of the embodiment of the present application can improve the initial efficiency and specific capacity through the Na phase with a suitable proportion and rich active sites, and can also improve the structural stability of the material during the electrochemical process, the cycling performance and gas generation behavior of the material by doping the cation M and the anion A.

[0075] In some embodiments, \(0 < y \leq 0.1\). In the lithium-sodium composite manganese-based material of the embodiment of the present application, the doping amount of Na cannot be higher than 20% of the total Li molar amount, that is, \(0 < y \leq 0.2\), optionally, \(0 < y \leq 0.1\), including but not limited to any one of the point values of 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2 or the range values between any two of them. If the doping amount of Na is higher than 20% of the total Li molar amount, it will exceed the limit that the graphite negative electrode in the traditional lithium-ion battery chemical system can withstand the Na ion throughput. Therefore, setting the doping amount of Na within a suitable range can meet the throughput limit of the negative electrode in the traditional lithium-ion battery.

[0076] In some embodiments, the mass percentage of the Na element in the lithium-sodium composite manganese-based material is greater than 0% and less than or equal to 6%; in other embodiments, the mass percentage of the Na element is greater than or equal to 0.3% and less than or equal to 2%. For example, the mass percentage of the Na element in the lithium-sodium composite manganese-based material includes but is not limited to 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.26%, 0.28%, 0.3%, 0.32%, 0.34%, 0.36%, 0.38%, 0.4%, 0.42%, 0.44%, 0.46%, 0.5%, 0.52%, 0.54%, 0.56%, 0.58%, 0.6%, any one of the point values ​​or the range value between any two of them. The mass percentage of Na element in the lithium-sodium composite manganese-based material can be obtained by inductively coupled plasma atomic emission spectrometry analysis.

[0077] In some embodiments, 0<x≤0.16. For example, x includes, but is not limited to, any one of 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, and 0.16, or a range of values ​​therebetween.

[0078] In some embodiments, t+y includes but is not limited to any one of 0.68, 0.7, 0.72, 0.74, 0.76, 0.78, 0.8, 0.82, 0.84, 0.86, 0.88, 0.9, 0.92, 0.94, 0.96, 0.98, 1, or a range of values ​​between any two of them.

[0079] In some embodiments, a includes but is not limited to any one of 0.17, 0.18, 0.2, 0.22, 0.24, 0.26, 0.28, 0.3, 0.32, 0.34, 0.36, 0.38, 4, or a range of values ​​therebetween.

[0080] In some embodiments, b includes but is not limited to any one of 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, or a range of values ​​between any two of them.

[0081] In some embodiments, c includes but is not limited to any one of 0.4, 0.42, 0.44, 0.46, 0.48, 0.5, 0.52, 0.54, 0.56, 0.58, 0.6, or a range of values ​​between any two of them.

[0082] In some embodiments, d includes but is not limited to any one of 0, 0.001, 0.002, 0.004, 0.006, 0.008, 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, or a range of values ​​therebetween.

[0083] In some embodiments, p includes but is not limited to any one of 0, 0.001, 0.002, 0.004, 0.006, 0.008, 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or a range of values ​​therebetween.

[0084] In some embodiments, q includes but is not limited to any one of 0.1, 0.2, 0.4, 0.6, 0.8, 1, 1.2, 1.4, 1.6, 1.8, 2, or a range of values ​​therebetween.

[0085] In some embodiments, the specific surface area of ​​the lithium sodium composite manganese-based material is 0.2 to 12 m 2 / g; In other embodiments, the specific surface area of ​​the lithium sodium composite manganese-based material is 0.4 to 10 m 2 / g, optionally 0.5~5.5m 2 / g. For example, the specific surface area of ​​lithium sodium composite manganese-based materials is not limited to 0.2m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g、1m 2 / g, 1.2m 2 / g, 1.4m 2 / g, 1.6m 2 / g, 1.8m 2 / g, 2m 2 / g, 2.2m 2 / g, 2.4m 2 / g, 2.6m 2 / g, 2.8m 2 / g、3m 2 / g, 3.2m 2 / g, 3.4m 2 / g, 3.6m 2 / g, 3.8m 2 / g、4m 2 / g, 4.2m 2 / g, 4.4m 2 / g, 4.6m 2 / g, 4.8m 2 / g、5m 2 / g, 5.2m 2 / g, 5.4m 2 / g, 5.5m 2 / g, 5.6m 2 / g, 5.8m 2 / g、6m 2 / g, 6.2m 2 / g, 6.4m 2 / g, 6.6m 2 / g, 6.8m 2 / g、7m 2 / g, 7.2m 2 / g, 7.4m 2 / g, 7.6m 2 / g、7.8m 2 / g、8m 2 / g, 8.2m 2 / g, 8.4m 2 / g, 8.6m 2 / g、9m 2 / g, 9.2m 2 / g, 9.4m 2 / g, 9.6m 2 / g, 9.8m 2 / g、10m 2 / g, 10.5m 2 / g、11m 2 / g, 11.5m 2 / g、12m 2 / g, or any range between them. Specific surface area can be determined using nitrogen adsorption specific surface area analysis, as described in GB / T 19587-2017, "Determination of Specific Surface Area of ​​Solids by BET Gas Adsorption." A suitable specific surface area range helps achieve higher gram capacity, initial coulombic efficiency, and cycle life, while also reducing gas production.

[0086] In some embodiments, the mass fraction of the alkaline substance in the lithium sodium manganese composite material is 250 to 3000 ppm; in other embodiments, the mass fraction of the alkaline substance in the lithium sodium manganese composite material is 300 to 3000 ppm, optionally 300 to 2000 ppm. For example, the mass fraction of alkaline substances in the lithium sodium composite manganese-based material includes, but is not limited to, any one of 250ppm, 300ppm, 350ppm, 400ppm, 450ppm, 500ppm, 550ppm, 600ppm, 650ppm, 700ppm, 750ppm, 800ppm, 850ppm, 900ppm, 950ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1600ppm, 1700ppm, 1800ppm, 1900ppm, 2000ppm, 2100ppm, 2200ppm, 2300ppm, 2400ppm, 2500ppm, 2600ppm, 2700ppm, 2800ppm, 2900ppm, and 3000ppm, or a range between any two of the values. In the embodiments of the present application, the alkaline substances in the lithium-sodium manganese composite material are also called residual alkali. The main components include alkaline substances such as lithium hydroxide, lithium carbonate, sodium hydroxide, and sodium carbonate. They are mainly derived from the lithium source and sodium source that are not sintered during the sintering process of preparing the lithium-sodium manganese composite material, or these alkaline substances are generated by decomposition during the sintering process. Specifically, the commonly used lithium sources for synthesizing lithium battery positive electrode materials include lithium hydroxide, lithium carbonate, etc., and a high lithium ratio is often used during the preparation process. Therefore, there will be residual alkali after the reaction, and the residual alkali exists in the form of lithium hydroxide, lithium carbonate, etc.; at the same time, the lithium-sodium manganese composite material of the embodiment of the present application is doped with sodium, and there may also be residual alkali during the doping process using the sodium source, forming residual alkali such as sodium hydroxide and sodium carbonate; in addition, alkali may also be precipitated inside the material during the preparation process. The mass fraction of alkaline substances can also be called residual alkali. The mass fraction of alkaline substances can be measured with reference to GB / T 9736-2008 "General method for determination of acidity and alkalinity of chemical reagents", and the standard solution is hydrochloric acid standard solution. The residual alkali amount has an important impact on the performance of the positive electrode material and the battery preparation process. The lithium sodium composite manganese-based material of the embodiment of the present application has a suitable residual alkali content, which helps to achieve lower internal resistance, higher gram capacity and ensure the processing performance of the positive electrode slurry.

[0087] In some embodiments, the X-ray diffraction pattern of the lithium sodium composite manganese-based material includes a (101) crystal plane diffraction peak at a 2θ angle of 36.5±0.5° and a (102) crystal plane diffraction peak at a 2θ angle of 38.4±0.5°, wherein the (101) crystal plane diffraction peak and the (102) crystal plane diffraction peak satisfy: (I 101 / I 102) 0.5 ≥1.96, where I 101 represents the peak area of ​​the (101) crystal plane diffraction peak, I 102 represents the peak area of ​​the (102) crystal plane diffraction peak; in other embodiments, (I 101 / I 102 ) 0.5 ≥2. For example, (I 101 / I 102 ) 0.5 Including but not limited to any one of 1.96, 1.97, 1.98, 1.99, 2, 2.01, 2.02, 2.03, 2.04, 2.05, 2.06, 2.08, 2.09, 3 or the range between any two of them.

[0088] X-ray diffraction technology uses the interaction between incident X-ray photons and electrons in the atoms of a sample to produce diffraction. This diffraction phenomenon is used to obtain the characteristic X-ray signal after diffraction, which is then processed to produce an X-ray diffraction pattern (XRD pattern). The diffraction peaks in an XRD pattern are produced by constructive interference of a monochromatic X-ray beam diffracted at specific angles from each set of lattice planes (crystal planes) in the sample. Therefore, the diffraction peaks in the XRD pattern correspond to the crystal planes of the sample. Furthermore, each diffraction peak in an XRD pattern satisfies the Bragg equation: 2dsinθ = nλ, where θ is the angle of incidence, d is the interplanar spacing, n is the diffraction order, λ is the wavelength of the incident beam, and 2θ is the diffraction angle. In an XRD pattern, the peak area of ​​a diffraction peak is the total area above the background line of the diffraction peak and represents the integrated intensity. The integrated intensity of a diffraction peak for a particular phase is proportional to the percentage of that phase in the sample, and therefore directly reflects the percentage of that phase in the compound. In actual operation, the peak area of ​​the diffraction peak is usually directly analyzed and calculated by XRD analysis software, such as the "Calculate Peak Area" function in MDI JADE software.

[0089] Oxygen defects are a key factor affecting cathode materials. These defects are caused by the detachment of oxygen atoms (oxygen ions) from the crystal lattice, resulting in oxygen vacancies. These defects can significantly impact material performance, such as the charge / discharge capacity, cycle performance, and rate capability of cathode materials.

[0090] For the lithium sodium manganese composite material of the present invention, the (101) crystal plane oxygen defect has no contribution, while the (102) crystal plane has a negative contribution to the oxygen defect. Therefore, the peak area ratio of the two crystal plane diffraction peaks can reflect the oxygen defect content and the presence of oxygen defects in the lithium sodium manganese composite material. In the present invention, (I 101 / I 102 )0.5 ≥1.96, which helps to form lithium-sodium manganese composite-based materials with lower oxygen defects, thereby improving the gram capacity, first efficiency, cycle performance and gas production of lithium-sodium manganese composite-based materials.

[0091] In some embodiments, the X-ray diffraction pattern of the lithium sodium composite manganese-based material includes a (002) crystal plane diffraction peak at a 2θ angle of 16.0±0.8° and a (003) crystal plane diffraction peak at a 2θ angle of 18.6±0.6°, wherein the (002) crystal plane diffraction peak and the (003) crystal plane diffraction peak satisfy: 0≤(I 002 / I 003 )≤0.4, where I 002 represents the peak area of ​​the (002) crystal plane diffraction peak, I 003 represents the peak area of ​​the (003) crystal plane diffraction peak; in other embodiments, 0.01≤(I 002 / I 003 )≤0.4. For example (I 002 / I 003 ) includes but is not limited to any one of 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, 0.22, 0.24, 0.26, 0.28, 0.3, 0.32, 0.34, 0.36, 0.38, 0.4 or any range between two of them. (002) and (003) crystal planes are related to the Na content, and suitable (I 002 / I 003 ) range helps to form a lithium-sodium composite manganese-based material with an appropriate proportion of Na-containing phases.

[0092] In some embodiments, the median particle size Dv50 of the lithium-sodium manganese composite material is 2 to 15 μm; in other embodiments, the median particle size Dv50 of the lithium-sodium manganese composite material is 3 to 10 μm. For example, the median particle size Dv50 of the lithium-sodium manganese composite material includes, but is not limited to, any one of 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm, and 15 μm, or a range of values ​​therebetween. Dv50, or median particle size, refers to the particle size at which the cumulative distribution of particles is 50%, indicating that 50% of the particles have diameters exceeding this value, and 50% of the particles have diameters below this value. The Dv50 of the particles can be tested with reference to GB / T 19077-2016 / ISO 13320:2009 "Particle size distribution laser diffraction method". In the embodiments of the present application, the particle morphology of the lithium sodium composite manganese-based material can be a regular sphere, or an ellipsoid, a polygon, or other irregular shapes. For spherical particles, the particle size is the diameter; for non-spherical or other irregularly shaped particles, the particle size is its equivalent particle size. The lithium sodium composite manganese-based material in the embodiments of the present application has a suitable median particle size, which is conducive to forming a suitable specific surface area, and the micron-level median particle size has low requirements for the preparation process, which helps to control costs.

[0093] In some embodiments, the particle size distribution span SPAN of the lithium sodium composite manganese-based material is in the range of [Dv90-Dv10) / Dv50]: 0.5≤SPAN≤2; in other embodiments, 0.5≤SPAN≤1.8, optionally 0.8≤SPAN≤1.4. For example, SPAN includes but is not limited to any point value among 0.5, 0.52, 0.54, 0.56, 0.58, 0.6, 0.62, 0.64, 0.66, 0.68, 0.7, 0.72, 0.74, 0.76, 0.78, 0.8, 0.82, 0.84, 0.86, 0.88, 0.9, 0.92, 0.94, 0.96, 0.98, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 2, or any range between any two of them. Dv90 represents the particle size corresponding to 90% of the cumulative particle size distribution of a sample. Its physical meaning is that particles with a particle size smaller than this particle size value account for 90% of all particles. Dv10 represents the particle size at which the cumulative distribution of particles is 10%, that is, the volume content of particles smaller than this particle size accounts for 10% of all particles. The particle size distribution span SPAN represents the distribution of particle size. The larger the SPAN, the wider the particle size distribution, and the smaller the SPAN, the more uniform the particle size distribution. Dv90 and Dv10 can be obtained by referring to GB / T 19077-2016 / ISO 13320:2009 "Particle size distribution laser diffraction method" test, and SPAN can be calculated based on the Dv90 and Dv10 obtained from the test. Particle size distribution has a great influence on the processing of positive electrode materials. The SPAN range of the embodiment of the present application helps to achieve a higher electrode compaction density.

[0094] In some embodiments, (t+x) / (a+b+c)=0.9-1.4, optionally (t+x) / (a+b+c)=1.3-1.4. For example, (t+x) / (a+b+c) includes but is not limited to any one of 0.9, 0.92, 0.94, 0.96, 0.98, 1, 1.1, 1.2, 1.3, 1.4, or a range of values ​​between any two of them. (t+x) / (a+b+c) represents the molar ratio of Li, Ni, Co, and Mn in the lithium-sodium manganese composite material. Under appropriate Li, Ni, Co, and Mn ratios, it is helpful to increase the mixing of cations in the lithium-sodium manganese composite material and improve the cycle performance.

[0095] The present invention also provides a method for preparing a lithium-sodium composite manganese-based material, comprising:

[0096] The raw materials are mixed and subjected to a first sintering process to obtain a lithium-sodium composite manganese-based material; the raw materials include a lithium source, a sodium source, a nickel source and a manganese source, and optionally also include a cobalt source, an M source and an A source;

[0097] Among them, the lithium-sodium composite manganese-based material includes Li t Na y [Li x Ni a Co b Mn c M d A p O q , 0 < y ≤ 0.2, 0.68 ≤ t + y ≤ 1, x + a + b + c + d = 1, x > 0, a ≥ 0.17, 0 ≤ b < 0.1, c ≥ 0.4, 0 ≤ d < 0.04, 0 ≤ p ≤ 0.1, 0 < q ≤ 2; M includes one or more of V, Nb, Ta, Cr, Mo, B, Al, Ti, Zr, Mg, Ce, Fe, W or Sn, and A includes one or more of F, S, N or Cl.

[0098] In the preparation method of the embodiment of the present application, first, the raw materials are mixed and subjected to the first sintering treatment, so that the Na element is doped into the lithium site, the M element is doped into the manganese site, and the A element is doped into the oxygen site, simultaneously realizing the doping of Na, M and A. The lithium-sodium composite manganese-based material prepared by this method has high specific capacity, high first Coulomb efficiency, good cycle performance, and the gas generation situation is effectively improved. At the same time, the preparation method of the embodiment of the present application is simple to operate, suitable for mass production, with low cost and high efficiency.

[0099] In some embodiments, the conditions of the first sintering treatment include one or more of the following (1) to (4):

[0100] (1) The temperature of the first sintering treatment is 700 - 1100 °C, optionally 750 - 1000 °C;

[0101] (2) Heating to the temperature of the first sintering treatment at a rate of 2 - 10 °C / min;

[0102] (3) Holding at the temperature of the first sintering treatment for 10 - 20 h;

[0103] (4) Oxygen-containing atmosphere.

[0104] In the embodiment of the present application, all "oxygen-containing atmospheres" involved refer to reaction atmospheres containing oxygen, where the volume percentage of oxygen in the atmosphere > 0. Exemplarily, the volume percentage of oxygen in the atmosphere can be set to 5% - 100%. In some embodiments, the volume percentage of oxygen can be 20% - 99.99%. In other embodiments, the oxygen-containing atmosphere can be air.

[0105] Appropriate sintering treatment conditions are conducive to the formation of composite oxide materials with high crystallinity and good doping effect by lithium source, sodium source, nickel source, cobalt source, manganese source, M source and A source, and the preparation of lithium-sodium composite manganese-based materials with high gram capacity, high first coulombic efficiency, cycle performance, and effectively improved gas production.

[0106] In some embodiments, the conditions of the first sintering process include one or more of the following (1) to (4):

[0107] (1) The temperature of the first sintering treatment is 780-990°C;

[0108] (2) heating to the first sintering temperature at a rate of 2-5°C / min;

[0109] (3) Maintaining the temperature at the first sintering treatment for 10 to 15 hours;

[0110] (4) An oxygen-containing atmosphere, wherein the volume percentage of oxygen in the oxygen-containing atmosphere is 20% to 99.99%.

[0111] More specifically, the temperature of the first sintering treatment includes but is not limited to any one of 700°C, 720°C, 740°C, 750°C, 760°C, 780°C, 800°C, 820°C, 840°C, 860°C, 880°C, 900°C, 920°C, 940°C, 960°C, 980°C, 990°C, 1000°C, 1100°C or a range between any two of them.

[0112] The rate of heating to the temperature of the first sintering treatment includes but is not limited to any one of 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, 5.5°C / min, 6°C / min, 6.5°C / min, 7°C / min, 7.5°C / min, 8°C / min, 8.5°C / min, 9°C / min, 9.5°C / min, and 10°C / min, or a range between any two of the values.

[0113] The holding time at the temperature of the first sintering treatment includes but is not limited to any one of 10h, 10.5h, 11h, 11.5h, 12h, 12.5h, 13h, 13.5h, 14h, 14.5h, 15h, 15.5h, 16h, 16.5h, 17h, 17.5h, 18h, 18.5h, 19h, 19.5h, and 20h, or a range between any two of them.

[0114] The volume percentage of oxygen in the oxygen-containing atmosphere includes, but is not limited to, any one of 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 99.99%, and 100%, or a range between any two of the values.

[0115] In some embodiments, the method for preparing the lithium-sodium composite manganese-based material further comprises a step of washing the product of the first sintering treatment.

[0116] After the first sintering treatment, alkaline substances (residual alkali) such as sodium hydroxide, lithium hydroxide, sodium carbonate, and lithium carbonate often remain. The amount of residual alkali has a significant impact on the performance of the positive electrode material and the battery manufacturing process. By performing a washing step after the first sintering treatment, the residual alkali content of the lithium-sodium manganese composite material can be adjusted, helping to achieve lower internal resistance, higher gram capacity, and ensure the processing performance of the positive electrode slurry.

[0117] In some embodiments, the washing step comprises: washing the product of the first sintering treatment with a washing liquid; the pH range of the washing liquid is 1.5 to 7; in other embodiments, the pH range of the washing liquid is 2 to 7, optionally 2.5 to 7. For example, the pH of the washing liquid includes, but is not limited to, any one of 1.5, 1.8, 2, 2.2, 2.4, 2.5, 2.6, 2.8, 3, 3.2, 3.4, 3.6, 3.8, 4, 4.2, 4.4, 4.6, 4.8, 5, 5.2, 5.4, 5.6, 5.8, 6, 6.2, 6.4, 6.6, 6.8, and 7, or any range therebetween.

[0118] Washing methods include, but are not limited to, rinsing and soaking. By treating the product of the first sintering treatment with an acidic or neutral washing solution, an acid-base neutralization reaction can occur, or the residual alkali concentration of the product of the first sintering treatment can be adjusted by washing and diluting to obtain a suitable residual alkali amount, which helps to achieve lower internal resistance, higher gram capacity, and ensure the processing performance of the positive electrode slurry.

[0119] In some embodiments, during the washing step, the solid-to-liquid ratio of the product of the first sintering treatment to the washing liquid is 1 / 35 to 1 / 6 g / mL; in other embodiments, the solid-to-liquid ratio of the product of the first sintering treatment to the washing liquid is 1 / 20 to 1 / 10 g / mL. For example, the solid-to-liquid ratio of the product of the first sintering treatment to the washing liquid includes, but is not limited to, any one of 1 / 35 g / mL, 1 / 30 g / mL, 1 / 25 g / mL, 1 / 20 g / mL, 1 / 15 g / mL, 1 / 10 g / mL, and 1 / 6 g / mL, or a range therebetween. A suitable solid-to-liquid ratio allows repeated washing of the product of the first sintering treatment to adjust the residual alkali content of the material.

[0120] In some embodiments, the washing treatment time is 0.2 to 10 hours; in other embodiments, the washing treatment time is 0.25 to 4 hours. For example, the washing treatment time includes but is not limited to any one of 0.2 hours, 0.25 hours, 0.3 hours, 0.35 hours, 0.4 hours, 0.5 hours, 0.6 hours, 0.7 hours, 0.8 hours, 0.9 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, and 10 hours, or any range therebetween. During the washing step, stirring, ultrasound, vibration, and other methods can be used to accelerate the process. For example, the washing step includes stirring at a rate of 800 to 1200 r / min, optionally 900 to 1000 r / min, specifically including but not limited to any of 800 r / min, 850 r / min, 900 r / min, 950 r / min, 1000 r / min, 1050 r / min, 1100 r / min, 1150 r / min, and 1200 r / min, or any range therebetween. By using appropriate washing conditions, the first sintered product can be repeatedly washed to adjust the residual alkali content of the material.

[0121] In some embodiments, the washing temperature is 10-60°C; in some embodiments, the washing temperature is 20-30°C, specifically including but not limited to any one of 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, and 60°C, or any range therebetween. The washing step can be performed under relatively mild conditions, even at room temperature, without the need for special heating, and is easy to operate and consumes little energy.

[0122] In some embodiments, the washing liquid includes one or more of water and an acid solution, including but not limited to a solution of any one or more of hydrochloric acid, sulfuric acid, nitric acid, acetic acid, citric acid, ammonium citrate, phosphoric acid, ammonium chloride, and ammonium sulfate (the solvent includes one or both of water and ethanol). Such an acid or acidic salt can form an acid solution to neutralize the product of the first sintering treatment without introducing impurity ions into the lithium-sodium composite manganese-based material.

[0123] In some embodiments, the method for preparing a lithium-sodium manganese composite material further includes performing a second sintering step on the product of the first sintering step. The second sintering step can improve the crystallinity and oxygen deficiency of the lithium-sodium manganese composite material, thereby improving the specific capacity, initial efficiency, cycle performance, and gas production of the lithium-sodium manganese composite material. In some embodiments, when the method for preparing a lithium-sodium manganese composite material includes both a washing step and a second sintering step, the second sintering step can be performed after the washing step.

[0124] In some embodiments, the conditions of the second sintering process include one or more of the following (i) to (iv):

[0125] (i) the temperature of the second sintering treatment is 300-700° C., optionally 300-600° C.;

[0126] (ii) heating the mixture to a second sintering temperature at a rate of 2 to 10° C. / min;

[0127] (iii) maintaining the temperature at the second sintering treatment for 5 to 20 hours;

[0128] (iv) Oxygen-containing atmosphere.

[0129] Carrying out a second sintering treatment under appropriate conditions can improve the crystallinity and oxygen defects of the lithium-sodium manganese composite-based material, which is beneficial to improving the gram capacity, first efficiency, cycle performance and gas production of the lithium-sodium manganese composite-based material.

[0130] In some embodiments, the conditions of the second sintering process include one or more of the following (i) to (iv):

[0131] (i) The temperature of the second sintering treatment is 400-550°C;

[0132] (ii) heating the mixture to a second sintering temperature at a rate of 2 to 5°C / min;

[0133] (iii) maintaining the temperature at the second sintering treatment for 8 to 12 hours;

[0134] (iv) an oxygen-containing atmosphere, wherein the volume percentage of oxygen in the oxygen-containing atmosphere is 20% to 99.99%.

[0135] More specifically, the temperature of the second sintering treatment includes but is not limited to any point value among 300℃, 320℃, 340℃, 360℃, 380℃, 400℃, 420℃, 440℃, 460℃, 480℃, 500℃, 520℃, 540℃, 550℃, 560℃, 580℃, 600℃, 620℃, 640℃, 660℃, 680℃, 700℃ or the range value between any two of them.

[0136] The rate of heating to the temperature of the second sintering treatment includes but is not limited to any one of 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, 5.5°C / min, 6°C / min, 6.5°C / min, 7°C / min, 7.5°C / min, 8°C / min, 8.5°C / min, 9°C / min, 9.5°C / min, and 10°C / min, or a range between any two of the values.

[0137] The holding time at the temperature of the second sintering treatment includes but is not limited to any one of 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h, 12h, 12.5h, 13h, 13.5h, 14h, 14.5h, 15h, 15.5h, 16h, 16.5h, 17h, 17.5h, 18h, 18.5h, 19h, 19.5h, and 20h, or a range between any two of them.

[0138] The volume percentage of oxygen in the oxygen-containing atmosphere includes, but is not limited to, any one of 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 99.99%, and 100%, or a range between any two of the values.

[0139] In some embodiments, the preparation method of the lithium-sodium manganese composite material further includes the step of controlling the particle size of the product of any one or more steps of the first sintering treatment, the washing treatment, and the second sintering treatment. Particle size control means that the particle size of the material is made to meet the requirements through one or more processes of crushing treatment, grinding treatment, ball milling treatment, and screening treatment. Controlling the particle size of the product of the first sintering treatment can facilitate full contact between the material and the washing liquid, which is beneficial to the adjustment of the residual alkali of the material. Controlling the particle size of the product of the washing treatment step can disperse the particles agglomerated in the washing treatment, which is beneficial to the second sintering treatment. After the washing treatment step, solid-liquid separation treatment and drying treatment can be carried out first, and then particle size control can be carried out. Controlling the particle size of the product of the second sintering treatment can make the lithium-sodium manganese composite material have a suitable particle size and particle size distribution, which is beneficial to the processing of the lithium-sodium manganese composite material and the realization of a higher pole piece compaction density.

[0140] In some embodiments, the lithium source includes one or more of lithium hydroxide, lithium carbonate, lithium acetate, lithium nitrate, lithium oxalate, and lithium sulfate.

[0141] In some embodiments, the sodium source includes one or more of sodium hydroxide, sodium carbonate, sodium acetate, sodium nitrate, sodium oxalate, sodium sulfate, sodium chloride, sodium tungstate, sodium fluoride, sodium sulfide, sodium peroxide, and sodium metaaluminate.

[0142] In some embodiments, the nickel source includes one or more of nickel hydroxide, nickel carbonate, nickel acetate, nickel nitrate, nickel oxalate, nickel sulfate, nickel chloride, nickel tungstate, nickel fluoride, nickel sulfide, and nickel-cobalt-manganese ternary composite hydroxide.

[0143] In some embodiments, the cobalt source includes one or more of cobalt hydroxide, cobalt carbonate, cobalt acetate, cobalt nitrate, cobalt oxalate, cobalt sulfate, cobalt chloride, cobalt tungstate, cobalt fluoride, cobalt sulfide, and nickel-cobalt-manganese ternary complex hydroxide.

[0144] In some embodiments, the manganese source includes one or more of manganese hydroxide, manganese carbonate, manganese acetate, manganese nitrate, manganese oxalate, manganese sulfate, manganese chloride, manganese tungstate, manganese fluoride, manganese sulfide, and nickel-cobalt-manganese ternary complex hydroxide.

[0145] The nickel-cobalt-manganese triple hydroxide in the nickel source, cobalt source and manganese source can provide nickel, cobalt and manganese at the same time. Its chemical formula is Ni x1 Co y1 Mn 1-x1-y1(OH)2, where x1 + y1 < 1, x1 > 0, y1 > 0; in some embodiments, 0 < x1 ≤ 0.4; in some embodiments, 0 < y1 ≤ 0.1. For example, x1 includes but is not limited to any one of the point values 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4 or the range values between any two of them; y1 includes but is not limited to any one of the point values 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, 0.045, 0.05, 0.055, 0.06, 0.065, 0.07, 0.075, 0.08, 0.085, 0.9, 0.095, 0.1 or the range values between any two of them.

[0146] In some embodiments, the atomic ratios of Ni, Co, and Mn in the nickel-cobalt-manganese ternary composite hydroxide are the same as those of Ni, Co, and Mn in the lithium-sodium composite manganese-based material Li t Na y [Li x Ni a Co b Mn c M d A p O q . In some embodiments, the nickel-cobalt-manganese ternary composite hydroxide can be used alone as the nickel source, cobalt source, and manganese source without selecting other nickel sources, cobalt sources, and manganese sources; in some embodiments, the nickel-cobalt-manganese ternary composite hydroxide can also be used simultaneously with other nickel sources, cobalt sources, and manganese sources to make the three elements of nickel, cobalt, and manganese satisfy the element dosage ratio of the chemical formula Li t Na y [Li x Ni a Co b Mn c M d A p O q .

[0147] In some embodiments, the M source includes one or more of the hydroxide of the M element, carbonate of the M element, acetate of the M element, nitrate of the M element, oxalate of the M element, sulfate of the M element, chloride of the M element, tungstate of the M element, fluoride of the M element, sulfide of the M element, and A compound of the M element.

[0148] In some embodiments, the A source includes one or more of the A compound of lithium, A compound of sodium, A compound of nickel, A compound of cobalt, A compound of manganese, and A compound of the M element.

[0149] Both the M source and the A source can be A compounds of the M element, which can provide both the M element and the A element. In some embodiments, the A compound of the M element can be used alone as both the M source and the A source, without using other M sources and A sources. In some embodiments, the A compound of the M element can also be used together with other M sources and A sources, so that the M and A elements satisfy the chemical formula Li t Na y [Li x Ni a Co b Mn c M d ]A p O q element dosage ratio.

[0150] An embodiment of the present application also provides a positive electrode plate, which includes the above-mentioned lithium-sodium composite manganese-based material or the lithium-sodium composite manganese-based material prepared by the above-mentioned method.

[0151] "Positive electrode" refers to the cathode of the battery, which contains positive electrode material, that is, active material. In lithium-ion batteries, during charging, lithium ions are released from the lattice of the positive electrode material and inserted into the lattice of the negative electrode material after passing through the electrolyte; during discharge, lithium ions are released from the lattice of the negative electrode material and inserted into the lattice of the positive electrode material after passing through the electrolyte. The lithium-sodium composite manganese-based material of the embodiment of the present application can be used as the active material of the positive electrode plate, which helps to achieve higher battery capacity, first coulomb efficiency and cycle performance, and improve battery gas production.

[0152] In some embodiments, the loading amount of the lithium sodium composite manganese-based material in the positive electrode sheet is 10 to 50 mg / cm 2 In other embodiments, the loading amount of the lithium sodium composite manganese-based material in the positive electrode sheet is 10 to 30 mg / cm 2 For example, the loading amount includes but is not limited to 10 mg / cm 2 、15mg / cm 2 , 20mg / cm 2 , 25mg / cm 2 、30mg / cm 2 、35mg / cm 2 , 40mg / cm 2 , 45mg / cm 2 、50mg / cm 2 The loading amount of the lithium sodium composite manganese-based material in the positive electrode sheet can also be flexibly set to other values ​​according to actual needs.

[0153] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer is combined with the positive electrode current collector; wherein the positive electrode active material layer contains the above-mentioned lithium sodium composite manganese-based material or the lithium sodium composite manganese-based material prepared as described above. The positive electrode current collector is a matrix on the electrode used to combine with the positive electrode active material layer. As the current collector of the positive electrode sheet, a metal current collector, a carbon current collector, a conductive resin current collector, a composite current collector of metal and resin, etc. can be selected, such as aluminum, nickel, stainless steel, carbon fiber, carbon nanotubes (CNT), graphite, etc. When the lithium sodium composite manganese-based material of the embodiment of the present application is used as a positive electrode active material, it is generally made into a positive electrode active material layer, and the positive electrode active material layer is combined with the current collector to form a complete positive electrode sheet. wherein, the positive electrode active material layer and the current collector can be combined in the following manner: the positive electrode active material layer is attached to one or both surfaces of the current collector; or the positive electrode active material layer is wrapped inside the current collector; or other combination methods.

[0154] In some embodiments, the positive electrode active material layer further includes one or both of a conductive agent and a binder. The conductive agent and / or the binder can form an electrode active layer together with the lithium sodium composite manganese-based material.

[0155] In the positive electrode sheet, the conductive agent collects microcurrents between the active materials and between the active materials and the current collector, improving electronic conductivity. At the same time, the conductive agent can also promote the wetting of the electrolyte into the positive electrode sheet. Example conductive agents include acetylene black (SP), carbon nanotubes, conductive carbon black (super-P), Ketjen black, carbon fiber, graphene, etc. The ratio of the conductive agent to the lithium sodium manganese composite material can be set according to needs and the ratios known in the art. As an example, the mass ratio of the conductive agent to the lithium sodium manganese composite material is 30 to 100:1; in some embodiments, the mass ratio of the conductive agent to the lithium sodium manganese composite material is 40 to 60:1. For example, the mass ratio of the conductive agent to the lithium sodium manganese composite material can include, but is not limited to, any one of 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, or a range between any two of them.

[0156] The binder is used to improve the bonding ability between the positive electrode active material layer and the current collector. Example binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), fluorinated rubber, polyethylene, polyethylene, polyurethane, etc. The ratio of the binder to the lithium sodium manganese composite material can be set according to needs and the ratios known in the art. As an example, the mass ratio of the binder to the lithium sodium manganese composite material is 30 to 100:1; in some embodiments, the mass ratio of the binder to the lithium sodium manganese composite material is 30 to 60:1. For example, the mass ratio of the binder to the lithium sodium manganese composite material may include but is not limited to any one of 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1 or a range between any two of them.

[0157] An embodiment of the present application further provides a secondary battery, which includes the above-mentioned positive electrode plate.

[0158] The positive electrode plate containing the lithium-sodium composite manganese-based material of the embodiment of the present application is applied to a secondary battery, and the secondary battery has high capacity, first coulombic efficiency and cycle performance, and low gas production.

[0159] In some embodiments, the secondary battery of the embodiments of the present application includes one or more of a battery cell, a battery module, and a battery pack. According to different packaging forms, secondary batteries are divided into battery cells, battery modules, and battery packs. Among them, the battery cell is the most basic unit of the secondary battery, including an electrode assembly and an electrolyte. The electrode assembly is usually composed of a positive electrode sheet, a negative electrode sheet, and an insulator. The battery cell mainly relies on the movement of metal ions in the electrolyte between the positive electrode sheet and the negative electrode sheet to work. In some battery packaging technologies, multiple battery cells can be integrated into a battery module first, and then the battery module can be installed in the battery box to form a battery pack. In other battery packaging technologies, multiple battery cells can also be directly installed in the box to form a battery pack, eliminating the intermediate state of the battery module, thereby reducing the mass of the battery pack and increasing the energy density of the battery.

[0160] In some embodiments, the secondary battery further includes a negative electrode plate. When the secondary battery is charged or discharged, the negative electrode plate and the positive electrode plate form a loop.

[0161] In some embodiments, the negative electrode plate may be a metal lithium plate.

[0162] In some embodiments, the negative electrode sheet may also include a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. For example, the negative electrode current collector includes two opposing surfaces in its thickness direction, and the negative electrode active material layer is laminated on either or both of the two surfaces of the negative electrode current collector.

[0163] In some embodiments, the negative electrode active material layer includes a negative electrode active material. As an example, the negative electrode active material can be natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, or a silicon-carbon composite.

[0164] In some embodiments, the negative electrode active material layer may further include a conductive agent and a binder. For example, the conductive agent may be one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers; and the binder may be one or more of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), water-based acrylic resin, and carboxymethyl cellulose (CMC).

[0165] In some embodiments, the negative active material layer may further optionally include a thickener, such as carboxymethyl cellulose (CMC).

[0166] In some embodiments, the negative electrode current collector may be made of a metal foil or porous metal plate with good electrical conductivity and mechanical properties, and may be made of one or more of copper, nickel, titanium, iron, and alloys thereof. For example, the negative electrode current collector is copper foil.

[0167] In some embodiments, the negative electrode sheet can be prepared according to conventional methods in the art. For example, the negative electrode active material, conductive agent, binder, and thickener are dispersed in a solvent, which can be N-methylpyrrolidone (NMP) or deionized water, to form a uniform negative electrode slurry. The negative electrode slurry is then coated on the negative electrode current collector. After drying and rolling, the negative electrode sheet is obtained.

[0168] In some embodiments, the secondary battery further includes an electrolyte, which can serve as a carrier for ion transport in the secondary battery and ensure that the reactions occurring during the operation of the secondary battery are reversible.

[0169] In some embodiments, the electrolyte may be a solid electrolyte, such as a polymer electrolyte, an inorganic solid electrolyte, etc., but is not limited thereto. The electrolyte may also be an electrolyte solution. The electrolyte solution includes a solvent and a lithium salt dissolved in the solvent.

[0170] The solvent may be a non-aqueous organic solvent, such as one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB) and ethyl butyrate (EB), preferably two or more.

[0171] The lithium salt may be one or more of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl imide), LiTFSI (lithium bis(trifluoromethanesulfonyl imide), LiTFS (lithium trifluoromethanesulfonyl imide), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium bis(oxalatoborate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorooxalatophosphate) and LiTFOP (lithium tetrafluorooxalatophosphate), for example, one or more of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiBOB (lithium bis(oxalatoborate), LiDFOB (lithium difluorooxalatoborate), LiTFSI (lithium bis(trifluoromethanesulfonyl imide)) and LiFSI (lithium bis(fluorosulfonyl imide).

[0172] The electrolyte may also optionally contain other additives, such as vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), succinonitrile (SN), adiponitrile (ADN), glutaronitrile (GLN), hexanetrinitrile (HTN), 1,3-propane sultone (1,3-PS), vinyl sulfate (DTD), methylene disulfonate (MMDS), 1-propylene-1,3-sultone (PST), 4-methylethylene sulfate (PCS), 4-ethylethylene sulfate (PES), 4-propylethylene sulfate (PEGLST), propylene sulfate (TS), 1,4-butane sultone (1,4-BS), ethylene sulfite (DTO), dimethyl sulfite (DMS), diethyl sulfite (DES), sulfonate cyclic quaternary ammonium salt, tris(trimethylsilyl) phosphate (TMSP) and tris(trimethylsilyl) borate (TMSB), but are not limited thereto.

[0173] In some embodiments, the secondary battery further includes a separator stacked between the positive and negative electrodes. In some secondary batteries, a separator is required to separate the positive and negative electrodes, preventing electrons from freely passing through the battery and short-circuiting the electrodes while allowing ions in the electrolyte to pass freely between the positive and negative electrodes.

[0174] The isolation membrane can be any known porous structure isolation membrane with electrochemical stability and mechanical stability, such as a single-layer or multi-layer film of one or more of glass fiber, non-woven fabric, polyethylene (PE), polypropylene (PP) and polyvinylidene fluoride (PVDF).

[0175] Positive and negative electrodes are alternately stacked, with a separator placed between them to provide insulation, to form a battery cell. Alternatively, the cell can be wound together. The cell is placed in a housing, injected with electrolyte, and sealed to create a lithium-ion secondary battery.

[0176] In addition, an embodiment of the present application further provides an electrical device, which includes the above-mentioned secondary battery.

[0177] The secondary battery disclosed in the embodiments of the present application can be used in electrical devices that use the battery as a power source, or various energy storage systems that use the battery as an energy storage element. Electrical devices may include, but are not limited to, mobile phones, tablets, laptops, electric toys, power tools, battery cars, electric cars, ships, spacecraft, and the like. Among them, electric toys may include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, and the like, and spacecraft may include airplanes, rockets, space shuttles, and spacecraft, and the like.

[0178] The following describes the details in conjunction with specific embodiments.

[0179] The test methods for the physicochemical and electrochemical properties of the materials involved in the examples of this application are as follows:

[0180] 1.XRD

[0181] The powder material was tested by X-ray diffraction pattern test using Bruker D8 Discovery equipment. The XRD pattern was obtained by slow scanning in the range of 10-70° at a scanning speed of 0.5° / min. The peak areas of the diffraction peaks at 2θ of 36.5±0.5°(101), 38.4±0.5°(102), 16.0±0.8°(002), and 18.6±0.6°(003) in the XRD pattern were calculated using software, and (I 101 / I 102 ) 0.5 and(I 002 / I003 ).

[0182] 2. Specific surface area test

[0183] The specific surface area test refers to GB / T 19587-2017 "Determination of the specific surface area of ​​solid materials by gas adsorption BET method", adopts the nitrogen adsorption specific surface area analysis test method, and is calculated by the BET (Brunauer Emmett Teller) method. The nitrogen adsorption specific surface area analysis test is performed by Micromeritics Tri-Star 3020 specific surface area pore size analyzer.

[0184] 3. Particle volume distribution particle size Dv10, Dv50, Dv90, SPAN

[0185] With reference to GB / T 19077-2016 / ISO 13320:2009 “Particle size distribution by laser diffraction method”, the Malvern 3000 instrument was used to measure Dv10, Dv50 and Dv90, and SPAN was calculated based on Dv10 and Dv90.

[0186] 4. Residual alkali potentiometric titration test

[0187] Referring to GB / T 9736-2008 "General method for determination of acidity and alkalinity of chemical reagents", weigh 10-30g of powder, add 100mL of pure water and stir for 30min. Let it stand for 10min and filter it. Then remove a certain amount of filtrate and select 0.05mol / L hydrochloric acid standard solution. Drain the liquid to expel the bubbles in the burette. Select the corresponding sensor and program to start the potentiometric titration test to calculate the residual alkali content of the lithium-sodium composite manganese-based material.

[0188] 5.Na content detection

[0189] Refer to EPA 6010D-2014 "Inductively Coupled Plasma Atomic Emission Spectrometry". Weigh the powder and digest it in 1+1 aqua regia. Use high temperature (about 200°C) for plate digestion. Element content (mass fraction w / w%) = element mass / sample weight * 100%.

[0190] 6. Initial gram capacity and first efficiency test method of button battery

[0191] At 2.5-4.55V, charge to 4.55V at 0.1C, then charge at 4.55V at constant voltage until the current is ≤ 0.05mA, let it stand for 5 minutes, the charge capacity at this time is recorded as C0, then discharge to 2.5V at 0.1C, the discharge capacity at this time is the initial gram capacity (first discharge gram capacity), recorded as D0, and the first efficiency is D0 / C0*100%.

[0192] 7. Full battery cycle performance test

[0193] Under constant temperature conditions of 25°C, at a voltage of 2.0V~4.45V, charge to 4.45V at a rate of 0.5C, then charge at constant voltage to a current ≤0.05mA, let it stand for 5 minutes, and then discharge to 2.0V at a rate of 0.5C. Record the discharge capacity and repeat the previous process to obtain the capacity retention rate after 500 cycles. Capacity retention rate = first cycle discharge capacity / discharge capacity at the specified number of cycles × 100%.

[0194] 8. Full battery 60℃ gas production test

[0195] At 60°C, store full batteries at 100% state of charge (SOC). Measure the open circuit voltage (OCV) and AC internal resistance (IMP) of the battery cells before, during, and after storage to monitor the state of charge (SOC), and measure the volume of the battery cells. Take out the full battery after every 48 hours of storage, test the OCV and IMP after standing for 1 hour, and measure the volume of the battery cells using the drainage method after cooling to room temperature. The drainage method is to first use a balance that automatically converts the dial data to measure the gravity F1 of the battery cells separately, and then completely place the battery cells in deionized water (density is known to be 1g / cm 3 ), measure the gravity F2 of the battery cell at this time, and the buoyancy F 浮 That is F1-F2, and then according to Archimedes principle F 浮 =ρgV 排 , V 排 is the drainage volume, and the cell volume V = V 排 =(F1-F2) / ρg.

[0196] After each volume test, the battery cell is recharged and charged to 4.45V at a constant current of 0.5C, and then charged at a constant voltage of 4.45V until the current drops to 0.05C. After the recharging is completed, it is put into the furnace to continue testing.

[0197] After 30 days of storage, the cell volume was measured, and the increase in cell volume after storage relative to the cell volume before storage, i.e., the gas production, was calculated.

[0198] Example 1

[0199] This embodiment provides a lithium sodium composite manganese-based material, the chemical formula of which is Li 0.847 Na 0.033 [Li 0.149 Ni 0.255 Co 0.043 Ce 0.002 Mn 0.551 ]F 0.002 O 1.999 , and its preparation method comprises the following steps:

[0200] Nickel, cobalt and manganese ternary composite hydroxide Ni 0.3 Co 0.05 Mn 0.65 (OH)2, lithium hydroxide, sodium oxalate, CeO2, and CeF3 were mixed in a high-speed mixer at a molar ratio of 1.0:1.17:0.06:0.001:0.001. The mixed materials were sintered once (first sintering) at a sintering temperature (first sintering temperature) of 900°C, a heating rate of 4°C / min, and a sintering time of 15 hours. The oxygen content (volume percentage) in the first sintering atmosphere was 65.00%, yielding an intermediate product 1 after the first sintering. The intermediate product 1 was mechanically ground and sieved to obtain a sintered material.

[0201] Ammonium citrate was dissolved in deionized water to prepare an acid solution with a pH of 2.57, and then acid washed with the weighed burnt material at a certain solid-liquid ratio (1 / 10 g / mL). The acid washing time was 0.5 h and the stirring rate was 900 r / min. After acid washing, the product was filtered, rinsed with deionized water, and filtered again. It was then dried at 80°C for 10 h. After mechanical grinding and vibration sieve treatment, the intermediate product 2 was obtained.

[0202] The intermediate product 2 obtained in the above step was placed in a furnace for secondary sintering (second sintering) at a sintering temperature (second sintering temperature) of 450° C., a heating rate of 2° C. / min, a sintering time of 10 hours, and an air atmosphere. The sintered material was mechanically ground and sieved to obtain a lithium-sodium manganese composite material. The lithium-sodium manganese composite material had a Dv50 of 6.5 μm and a SPAN of 1.15.

[0203] Examples 2 to 4

[0204] Examples 2 to 4 respectively provide a lithium-sodium composite manganese-based material, the chemical formula of which is shown in Table 1.

[0205] The difference between the preparation methods of the lithium sodium composite manganese-based materials in Examples 2 to 4 and Example 1 is that the proportion of the Na source (ie, sodium oxalate) is adjusted.

[0206] Specifically, the raw materials of Example 2 include Ni in molar ratio. 0.3 Co 0.05 Mn 0.65 (OH)2: lithium hydroxide: sodium oxalate: CeO2: CeF3 = 1.0: 1.17: 0.020: 0.001: 0.001; the raw materials of Example 3 include Ni in molar ratio. 0.3 Co 0.05 Mn 0.65(OH)2: lithium hydroxide: sodium oxalate: CeO2: CeF3 = 1.0: 1.15: 0.20: 0.001: 0.001; the raw materials of Example 4 include Ni in molar ratio. 0.3 Co 0.05 Mn 0.65 (OH)2:lithium hydroxide:sodium oxalate:CeO2:CeF3=1.0:0.96:0.39:0.001:0.001.

[0207] The other steps are the same as those in Example 1.

[0208] Examples 5-6

[0209] Examples 5 and 6 respectively provide a lithium-sodium composite manganese-based material, the chemical formula of which is shown in Table 1.

[0210] The difference between the preparation methods of the lithium sodium composite manganese-based materials in Examples 5 and 6 and that in Example 1 is that the raw materials do not contain a Ce source or a F source.

[0211] Specifically, the raw materials of Example 5 include Ni in molar ratio. 0.3 Co 0.05 Mn 0.65 (OH)2: lithium hydroxide: sodium oxalate: NH4F = 1.0: 1.17: 0.06: 0.12; the raw materials of Example 6 include Ni in molar ratio 0.3 Co 0.05 Mn 0.65 (OH)2:lithium hydroxide:sodium oxalate:CeO2=1.0:1.17:0.06:0.002.

[0212] The other steps are the same as those in Example 1.

[0213] Examples 7-8

[0214] Examples 7 and 8 respectively provide a lithium-sodium composite manganese-based material, the chemical formula of which is shown in Table 1.

[0215] The difference between the preparation methods of the lithium sodium manganese composite material in Examples 7 and 8 and that in Example 1 is that the amounts of Ce and F in the raw materials are adjusted so that the chemical formula of the lithium sodium manganese composite material satisfies the corresponding chemical formula.

[0216] The other steps are the same as those in Example 1.

[0217] Examples 9-11

[0218] Examples 9 to 11 respectively provide a lithium-sodium composite manganese-based material, the chemical formula of which is shown in Table 1.

[0219] The preparation methods of the lithium sodium composite manganese-based materials in Examples 9 to 11 differ from those in Example 1 in that Ce is replaced by Sb or Mo, and F is replaced by S; or F is replaced by Cl alone.

[0220] The other steps are the same as those in Example 1.

[0221] Examples 12 to 14

[0222] Examples 12 to 14 respectively provide a lithium-sodium composite manganese-based material, the chemical formula of which is the same as that of Example 1, as shown in Table 1.

[0223] The difference between the preparation methods of the lithium sodium composite manganese-based materials in Examples 12 to 14 and Example 1 is that the first sintering temperature is changed. Specifically, the first sintering temperatures in Examples 12 to 14 are 780° C., 920° C., and 990° C., respectively.

[0224] The other steps are the same as those in Example 1.

[0225] Examples 15 to 18

[0226] Examples 15 to 18 respectively provide a lithium-sodium composite manganese-based material, the chemical formula of which is the same as that of Example 1, as shown in Table 1.

[0227] The preparation methods of the lithium sodium manganese composite materials in Examples 15 to 18 differ from those in Example 1 in that the pH value of the acid solution is changed. Specifically, the pH values ​​of the acid solution in Examples 15 to 18 are 2, 2.5, 5.5, and 7, respectively.

[0228] The other steps are the same as those in Example 1.

[0229] Examples 19 to 21

[0230] Examples 19 to 21 respectively provide a lithium-sodium composite manganese-based material, the chemical formula of which is the same as that of Example 1, as shown in Table 1.

[0231] The preparation methods of the lithium-sodium manganese composite materials in Examples 19 to 21 differ from those in Example 1 in that the second sintering temperature is changed. Specifically, the second sintering temperatures in Examples 19 to 21 are 300° C., 500° C., and 600° C., respectively.

[0232] The other steps are the same as those in Example 1.

[0233] Examples 22 to 24

[0234] Examples 22 to 24 respectively provide a lithium-sodium composite manganese-based material, the chemical formula of which is the same as that of Example 1, as shown in Table 1.

[0235] The preparation methods of the lithium-sodium manganese composite materials in Examples 22-24 differ from those in Example 1 in that the mechanical grinding and sieve vibration treatment parameters after the first sintering are adjusted to change the Dv50 of the lithium-sodium manganese composite materials. Specifically, the Dv50 of the lithium-sodium manganese composite materials in Examples 22-24 are 3 μm, 10 μm, and 15 μm, respectively.

[0236] The other steps are the same as those in Example 1.

[0237] Examples 25 to 28

[0238] Examples 25 to 28 respectively provide a lithium-sodium composite manganese-based material, the chemical formula of which is the same as that of Example 1, as shown in Table 1.

[0239] The preparation methods of the lithium-sodium manganese composite materials in Examples 25-28 differ from those in Example 1 in that the mechanical grinding and sieving parameters after the first sintering step are adjusted so that the Dv50 of the lithium-sodium manganese composite materials remains unchanged, but the SPAN is changed. Specifically, the SPAN of the lithium-sodium manganese composite materials in Examples 25-28 are 0.5, 0.8, 1.4, and 1.8, respectively.

[0240] The other steps are the same as those in Example 1.

[0241] Examples 29-30

[0242] Examples 29 to 30 respectively provide a lithium-sodium composite manganese-based material, the chemical formula of which is the same as that of Example 1, as shown in Table 1.

[0243] The difference between the preparation methods of the lithium sodium manganese composite material in Examples 29-30 and Example 1 is that the first sintering oxygen content is adjusted. Specifically, the first sintering oxygen content in Examples 29-30 is 20.93% and 99.99%, respectively.

[0244] The other steps are the same as those in Example 1.

[0245] Examples 31-32

[0246] Examples 31-32 respectively provide a lithium-sodium composite manganese-based material, the chemical formula of which is shown in Table 1.

[0247] The difference between the preparation method of the lithium sodium composite manganese-based material in Examples 31-32 and Example 1 is that the ratio of Ni, Co, and Mn in the nickel-cobalt-manganese ternary composite hydroxide and the ratio of the nickel-cobalt-manganese ternary composite hydroxide to other raw materials are changed. Specifically, the raw materials in Example 31 include Ni, Co, and Mn in molar ratio. 0.40 Mn 0.60(OH)2: lithium hydroxide: sodium oxalate: CeO2: CeF3 = 1.0: 1.065: 0.165: 0.001: 0.003; the raw materials in Example 32 include Ni in molar ratio. 0.22 Co 0.08 Mn 0.70 (OH)2:lithium hydroxide:sodium oxalate:CeO2:CeF3=1.0:1.299:0.150:0.001:0.001.

[0248] The other steps are the same as those in Example 1.

[0249] Examples 33-34

[0250] Examples 33 to 34 respectively provide a lithium-sodium composite manganese-based material, whose chemical formula is the same as that of Example 1, as shown in Table 1.

[0251] The difference between the preparation methods of the lithium sodium composite manganese-based materials in Examples 33 and 34 and Example 1 is that the first sintering temperature is changed. Specifically, the first sintering temperatures in Examples 33 and 34 are 700° C. and 1100° C., respectively.

[0252] The other steps are the same as those in Example 1.

[0253] Example 35

[0254] Example 35 provides a lithium-sodium composite manganese-based material, the chemical formula of which is shown in Table 1.

[0255] The preparation method of the lithium-sodium composite manganese-based material in Example 35 differs from that in Example 1 in that the ratio between the lithium source and the sodium source is changed (the lithium source is reduced while the sodium source is increased), and the pH of the acid solution is lowered to 1.5.

[0256] Specifically, the raw materials in Example 35 include Ni 0.3 Co 0.05 Mn 0.65 (OH)2:lithium hydroxide:sodium oxalate:CeO2:CeF3=1.0:0.96:0.39:0.001:0.001, the pH of the acid solution is 1.5.

[0257] Comparative Example 1

[0258] This comparative example 1 provides a composite manganese-based material, the chemical formula of which is shown in Table 1.

[0259] The difference between the composite manganese-based material in Comparative Example 1 and Example 1 is that no Na is doped. Correspondingly, in the preparation method of the composite manganese-based material in Comparative Example 1, the raw material does not contain sodium oxalate.

[0260] The other steps are the same as those in Example 1.

[0261] Comparative Example 2

[0262] This comparative example 2 provides a lithium-sodium composite manganese-based material, the chemical formula of which is shown in Table 1.

[0263] The lithium sodium composite manganese-based material in Comparative Example 2 differs from that in Example 1 in that the doping amount of Na is increased so that t+y in the chemical formula is less than 0.68.

[0264] Correspondingly, in the preparation method of the lithium sodium composite manganese-based material in Comparative Example 2, the proportion of the raw material sodium oxalate is increased. Specifically, the raw materials in Comparative Example 2 include Ni 0.3 Co 0.05 Mn 0.65 (OH)2:lithium hydroxide:sodium oxalate:CeO2:CeF3=1.0:0.37:0.98:0.001:0.001.

[0265] The other steps are the same as those in Example 1.

[0266] Comparative Example 3

[0267] This comparative example 3 provides a lithium-sodium composite manganese-based material, the chemical formula of which is shown in Table 1.

[0268] The lithium-sodium manganese composite material in Comparative Example 3 differs from Example 1 in that the Co content is increased so that b in its chemical formula is greater than 0.1, and the contents of other elements are adaptively adjusted to meet the requirements for lattice stability. Accordingly, the chemical formula in the preparation method of the lithium-sodium manganese composite material in Comparative Example 3 adaptively adjusts the ratio of the raw materials.

[0269] The other steps are the same as those in Example 1.

[0270] Comparative Example 4

[0271] This comparative example 4 provides a lithium-sodium composite manganese-based material, the chemical formula of which is shown in Table 1.

[0272] The difference between the lithium sodium composite manganese-based material in Comparative Example 4 and Example 1 is that the Ce content is increased so that d in its chemical formula is ≥ 0.04. Correspondingly, the chemical formula in the preparation method of the lithium sodium composite manganese-based material in Comparative Example 4 is adaptively adjusted to the ratio of raw materials. Specifically, the raw materials in Comparative Example 4 include Ni 0.3 Co 0.05 Mn 0.65 (OH)2:lithium hydroxide:sodium oxalate:CeO2:CeF3=1.0:0.37:0.98:0.05:0.001.

[0273] The other steps are the same as those in Example 1.

[0274] Comparative Example 5

[0275] This comparative example 5 provides a lithium-sodium composite manganese-based material, the chemical formula of which is shown in Table 1.

[0276] The difference between the lithium sodium composite manganese-based material in Comparative Example 5 and Example 1 is that the content of F is increased so that p in the chemical formula is greater than 0.1. Correspondingly, the chemical formula in the preparation method of the lithium sodium composite manganese-based material in Comparative Example 5 is adaptively adjusted to the ratio of raw materials. Specifically, the raw materials in Comparative Example 5 include Ni 0.3 Co 0.05 Mn 0.65 (OH)2:lithium hydroxide:sodium oxalate:CeO2:NH4F=1.0:0.37:0.98:0.002:0.235.

[0277] The other steps are the same as those in Example 1.

[0278] Comparative Example 6

[0279] Comparative Example 6 provides a lithium-sodium composite manganese-based material, the chemical formula of which is shown in Table 1.

[0280] The difference between the preparation method of the lithium sodium composite manganese-based material in Comparative Example 6 and that in Example 1 is that the ratio between the lithium source and the sodium source is changed (the lithium source is reduced and the sodium source is increased). Specifically, the raw materials in Comparative Example 6 include Ni 0.3 Co 0.05 Mn 0.65 (OH)2:lithium hydroxide:sodium oxalate:CeO2:CeF3=1.0:0.77:0.06:0.001:0.001, so that t+y in the chemical formula of Comparative Example 6 is less than 0.68.

[0281] The other steps are the same as those in Example 1.

[0282] The chemical formula and element content of the lithium sodium composite manganese-based material (or composite manganese-based material) in each embodiment and comparative example are shown in Table 1. At the same time, some preparation parameters of the lithium sodium composite manganese-based material (or composite manganese-based material) in each embodiment and comparative example are shown in Table 2.

[0283] Table 1. Chemical formula and element content of lithium sodium composite manganese-based materials (or composite manganese-based materials)

[0284] Table 2. Preparation parameters of lithium sodium composite manganese-based materials (or composite manganese-based materials)

[0285] The structure and performance of the lithium-sodium composite manganese-based materials (or composite manganese-based materials) of each embodiment and comparative example were characterized, including BET specific surface area, SPAN, Dv50, sodium mass percentage (Na%), residual alkali content (i.e., mass fraction of alkaline substances), and key diffraction peak area ratios in the X-ray diffraction pattern. The results are shown in Table 3 below.

[0286] Table 3. Structure and performance characterization results of lithium-sodium composite manganese-based materials (or composite manganese-based materials)

[0287] Electrochemical performance test

[0288] The lithium sodium composite manganese-based materials (or composite manganese-based materials) of the above embodiments and comparative examples were used as positive electrode active materials to make positive electrode sheets, which were assembled into lithium-ion batteries and then subjected to electrochemical performance tests.

[0289] Specifically, the lithium sodium composite manganese-based materials (or composite manganese-based materials) of each embodiment and comparative example were respectively put into a 5L stirring tank for premixing for 30 minutes, and then the conductive agent acetylene black (SP) and the binder polyvinylidene fluoride (PVDF) were added for secondary dry mixing for 30 minutes. Finally, the solvent N-methylpyrrolidone (NMP) was added and rapidly stirred under vacuum conditions to form a slurry. Among them, the mass ratio of positive electrode active material: acetylene black: polyvinylidene fluoride = 96:2:2, and the solid content of the slurry is 70wt%. The slurry was evenly coated on both sides of an aluminum foil with a thickness of 12μm. The coated electrode was taken out after drying in a 130°C oven for half an hour to obtain a positive electrode plate. Among them, the positive electrode active material loading of the positive electrode plate is 21.5mg / cm 2 The negative electrode active material artificial graphite, hard carbon, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener carbon methyl cellulose sodium (CMC) were thoroughly stirred and mixed in a deionized water solvent system at a mass ratio of 90:5:2:2:1, and then coated on copper foil, dried, and cold pressed to obtain a negative electrode sheet.

[0290] A polyethylene porous polymer film is used as a separator. The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator positioned between the positive and negative electrodes to provide isolation. The cells are then wound to form a bare cell. The bare cell is placed in an outer packaging and filled with a prepared basic electrolyte solution (1 mol / L LiPF6 / (EC+EMC+DMC) in a 1:1:1 volume ratio). The cell is then packaged to produce a lithium-ion battery.

[0291] The assembled lithium-ion battery was tested, and the test results are shown in Table 4 below.

[0292] Table 4. Electrochemical test results of lithium-sodium composite manganese-based materials (or composite manganese-based materials) assembled batteries

[0293] Tables 1 to 4 reflect the following:

[0294] Examples 1 to 35 show that after appropriate amounts of Na, M (optionally including Ce, Sb, Mo, etc.) and A (optionally including F, S, Cl, etc.) are added to the lithium-sodium manganese composite material, the lithium-sodium manganese composite material has a lower residual alkali concentration; after such lithium-sodium manganese composite material is used as the positive electrode active material, the positive electrode has a very high discharge capacity and first efficiency; and has a very high capacity retention rate after 500 cycles at room temperature, and has excellent cycle performance; the gas production after storage at a high temperature of 60°C for 30 days is low, and the safety is good.

[0295] In contrast, as reflected in Comparative Example 1, when no Na is doped in the composite manganese-based material, the first discharge gram capacity and first effect of the positive electrode are significantly reduced. The first discharge gram capacity is reduced by 3.98% to 5.65% compared with the case of Na doping under the same conditions (Comparative Example 1 compared with Examples 1 to 4), and the first effect is reduced by 1.2% to 3.5% compared with the case of Na doping under the same conditions.

[0296] As reflected in Comparative Example 2, after excessive Na is doped into the lithium-sodium composite manganese-based material, there are defects such as reduced first discharge capacity, reduced cycle performance, and increased gas production.

[0297] Comparative Example 3 shows that if the Co content in the lithium-sodium composite manganese-based material is too low, the first discharge gram capacity of the positive electrode will be reduced.

[0298] Comparative Examples 4 and 5 show that after excessive doping of M or A into the lithium-sodium composite manganese-based material, the first discharge gram capacity and first efficiency of the positive electrode will be reduced.

[0299] Comparative Example 6 further reflects that the inappropriate content of lithium and sodium in the lithium-sodium composite manganese-based material will not only significantly reduce the cycle performance of the positive electrode and significantly increase the gas production, but also reduce the first charge and discharge capacity and first efficiency of the positive electrode.

[0300] Therefore, the embodiment of the present application satisfies the requirement of Li by adding appropriate amounts of Na, M, and A into the lithium sodium composite manganese-based material. t Na y [Li x Ni a Co b Mn c M d ]A p O q, where \(0 \lt y \leq 0.2\), \(0.68 \leq t + y \leq 1\), \(x + a + b + c + d = 1\), \(x \gt 0\), \(a \geq 0.2\), \(0 \leq b \lt 0.1\), \(c \geq 0.4\), \(0 \leq d \lt 0.04\), \(0 \leq p \leq 0.1\), \(0 \lt q \leq 2\), which can enable the positive electrode with this lithium-sodium composite manganese-based material as the active material to simultaneously have a very high discharge capacity per gram and initial efficiency, as well as excellent cycle performance and low gas production, and has very good comprehensive performance.

[0301] Finally, it should be noted that: the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it; although the present application has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that: they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be covered within the scope of the claims and the description of the present application. In particular, as long as there is no structural conflict, the technical features mentioned in each embodiment can be combined in any way. The present application is not limited to the specific embodiments disclosed in the text, but includes all technical solutions falling within the scope of the claims.

Claims

1. A lithium sodium composite manganese-based material, characterized in that: The lithium-sodium composite manganese-based material includes Li t Na y [Li x Ni a Co b Mn c M d A p O q , where 0 < y ≤ 0.2, 0.68 ≤ t + y ≤ 1, x + a + b + c + d = 1, x > 0, a ≥ 0.17, 0 ≤ b < 0.1, c ≥ 0.4, 0 ≤ d < 0.04, 0 ≤ p ≤ 0.1, 0 < q ≤ 2; M includes one or more of V, Nb, Ta, Cr, Mo, B, Al, Ti, Zr, Mg, Ce, Fe, W or Sn; A includes one or more of F, S, N or Cl.

2. The lithium-sodium composite manganese-based material according to claim 1, characterized in that: 0<y≤0.1; And / or, (t+x) / (a+b+c)=0.9-1.4, optionally (t+x) / (a+b+c)=1.3-1.

4.

3. The lithium-sodium composite manganese-based material according to claim 1 or 2, characterized in that: The mass percentage of the Na element in the lithium-sodium composite manganese-based material is less than or equal to 6%; optionally greater than or equal to 0.3% and less than or equal to 2%.

4. The lithium-sodium composite manganese-based material according to any one of claims 1 to 3, characterized in that: The specific surface area of ​​the lithium sodium composite manganese-based material is 0.3 to 12 m 2 / g; optionally 0.4~10m 2 / g; optionally 0.5~5.5m 2 / g.

5. The lithium-sodium composite manganese-based material according to any one of claims 1 to 4, characterized in that: The mass fraction of alkaline substances in the lithium-sodium composite manganese-based material is 250-3000 ppm; optionally 300-3000 ppm; optionally 300-2000 ppm.

6. The lithium-sodium composite manganese-based material according to any one of claims 1 to 5, characterized in that: The X-ray diffraction spectrum of the lithium sodium composite manganese-based material includes a (101) crystal plane diffraction peak located at a 2θ angle of 36.5±0.5° and a (102) crystal plane diffraction peak located at a 2θ angle of 38.4±0.5°, and the (101) crystal plane diffraction peak and the (102) crystal plane diffraction peak satisfy the following conditions: (I 101 / I 102 ) 0.5 ≥1.96, where I 101 represents the peak area of ​​the (101) crystal plane diffraction peak, the I 102 represents the peak area of ​​the (102) crystal plane diffraction peak; optionally, (I 101 / I 102 ) 0.5 ≥2.

7. The lithium-sodium composite manganese-based material according to any one of claims 1 to 6, characterized in that: The X-ray diffraction spectrum of the lithium sodium composite manganese-based material includes a (002) crystal plane diffraction peak at a 2θ angle of 16.0±0.8° and a (003) crystal plane diffraction peak at a 2θ angle of 18.6±0.6°, and the (002) crystal plane diffraction peak and the (003) crystal plane diffraction peak satisfy: 0≤(I 002 / I 003 )≤0.4, where I 002 represents the peak area of ​​the (002) crystal plane diffraction peak, I 003 represents the peak area of ​​the (003) crystal plane diffraction peak; optionally, 0.01≤(I 002 / I 003 )≤0.

4.

8. The lithium-sodium composite manganese-based material according to any one of claims 1 to 7, characterized in that: The median particle size Dv50 of the lithium sodium composite manganese-based material is 2 to 15 μm; optionally, 3 to 10 μm.

9. The lithium-sodium composite manganese-based material according to any one of claims 1 to 8, characterized in that: The particle size distribution span SPAN of the lithium-sodium composite manganese-based material = [(Dv90-Dv10) / Dv50] value range: 0.5≤SPAN≤2; optionally, 0.5≤SPAN≤1.8; optionally, 0.8≤SPAN≤1.

4.

10. A method for preparing a lithium-sodium composite manganese-based material, characterized in that: include: The raw materials are mixed and subjected to a first sintering process to obtain a lithium-sodium composite manganese-based material; the raw materials include a lithium source, a sodium source, a nickel source and a manganese source, and optionally also include a cobalt source, an M source and an A source; Among them, the lithium-sodium composite manganese-based material includes Li t Na y [Li x Ni a Co b Mn c M d A p O q , 0 < y ≤ 0.2, 0.68 ≤ t + y ≤ 1, x + a + b + c + d = 1, x > 0, a ≥ 0.17, 0 ≤ b < 0.1, c ≥ 0.4, 0 ≤ d < 0.04, 0 ≤ p ≤ 0.1, 0 < q ≤ 2; M includes one or more of V, Nb, Ta, Cr, Mo, B, Al, Ti, Zr, Mg, Ce, Fe, W or Sn, and A includes one or more of F, S, N or Cl.

11. The method for preparing the lithium sodium composite manganese-based material according to claim 10, characterized in that: The conditions of the first sintering treatment include one or more of the following (1) to (4): (1) The temperature of the first sintering treatment is 700-1100° C., optionally 750-1000° C., optionally 780-990° C.; (2) heating to the temperature of the first sintering treatment at a rate of 2 to 10° C. / min, optionally, the rate is 2 to 5° C. / min; (3) maintaining the temperature at the first sintering treatment for 10 to 20 hours, or optionally 10 to 15 hours; (4) An oxygen-containing atmosphere. Optionally, the volume percentage of oxygen in the oxygen-containing atmosphere is 20% to 99.99%.

12. The method for preparing the lithium sodium composite manganese-based material according to claim 10 or 11, characterized in that: The preparation method further comprises a step of washing the product of the first sintering treatment; Optionally, the washing treatment step includes: washing the product of the first sintering treatment with a washing liquid; Optionally, the pH range of the washing liquid is 1.5 to 7, optionally 2 to 7, optionally 2.5 to 7; Optionally, the solid-liquid ratio of the product of the first sintering treatment to the washing liquid is 1 / 35 to 1 / 6 g / mL, and optionally 1 / 20 to 1 / 10 g / mL; Optionally, the washing treatment time is 0.2 to 10 hours, optionally 0.25 to 4 hours; Optionally, the washing process includes a stirring step, and the stirring rate is 800 to 1200 r / min, and optionally 900 to 1000 r / min; Optionally, the washing liquid includes one or more of water and acid; optionally, the acid includes any one or more solutions of hydrochloric acid, sulfuric acid, nitric acid, acetic acid, citric acid, ammonium citrate, phosphoric acid, ammonium chloride, and ammonium sulfate.

13. The method for preparing the lithium sodium composite manganese-based material according to any one of claims 10 to 12, characterized in that: The preparation method further comprises a step of performing a second sintering treatment on the product of the first sintering treatment; Optionally, the conditions of the second sintering treatment include one or more of the following (i) to (iv): (i) the temperature of the second sintering treatment is 300-700° C., optionally 300-600° C., optionally 400-550° C.; (ii) heating to the temperature of the second sintering treatment at a rate of 2 to 10° C. / min, optionally at a rate of 2 to 5° C. / min; (iii) maintaining the temperature of the second sintering treatment for 5 to 20 hours, optionally 8 to 12 hours; (iv) an oxygen-containing atmosphere, wherein the volume percentage of oxygen in the oxygen-containing atmosphere is 20% to 99.99%.

14. A positive electrode sheet, characterized in that: The positive electrode plate comprises the lithium-sodium composite manganese-based material according to any one of claims 1 to 9, or comprises the lithium-sodium composite manganese-based material prepared by the method according to any one of claims 10 to 13.

15. A secondary battery, characterized in that: The secondary battery comprises the positive electrode sheet as claimed in claim 14.

16. An electrical device, characterized in that: The electric device comprises the secondary battery as claimed in claim 15.